Pemphigus vulgaris - Vijeev Vasudevan; Vadi V Bharathan; Radhika (Wolters Kluwer Medknow Publications, 2008)
Pemphigus vulgaris is the most common form of Pemphigus, is an autoimmune disease of the skin and mucous membrane characterized by impaired cell adhesion within the epidermis leading to the formation of intraepidermal bullae. The exact cause of the development of antibodies against the body's own tissues is unknown. Most patients are initially misdiagnosed and improperly treated.Diagnosis is mostly based on appearance and distribution of the skin lesions. Definitive diagnosis requires examination of a skin biopsy for histopathology and immunofluroscent study. Dental professionals must be sufficiently familiar with the clinical manifestations of pemphigus vulgaris to ensure early diagnosis and treatment, since this in turn determines the prognosis and course of the disease. Hence, we report a case of pemphigus vulgaris that was misdiagnosed in its early stage.